THE CONTENT OF EXPERIMENTAL TEACHING OF FUTURE PROGRAMMERS IN FORMING FOREIGN LANGUAGE COMMUNICATION SKILLS WITHIN COMFORTABLE LEARNING ENVIRONMENT - Ірина Семиряк (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The problem of foreign language communicative skills building in the conditions of a comfortable learning environment has been considered. Specific features of virtual learning environment construction and operation have been analysed. The content of experimental learning for future programmers with the focus on building their foreign language communicative skills in the conditions of a comfortable learning environment, organised on the basis of the Department of Foreign Languages for Sciences, Lviv National Ivan Franko University, has been characterised in detail.